Dari Minoritas ke Mayoritas: Asimilasi dan Integrasi Orang Indo-Eropa di Indonesia, 1950-1959 - Rooyackers, Max (Department of History, Faculty of Humanities, Diponegoro University, 2024)
This study investigates the integration and assimilation trajectories of Indonesian citizens of European descent in the aftermath of the national revolution. Focusing on the Partai Indo Nasional (PIN) and the Indo-Eenheids Verbond (IEV), later transformed into the Gabungan Indo untuk Kesatuan Indonesia (GIKI-IEV), the research explores the divergent strategies adopted by these two prominent organizations to navigate their post-colonial identity. While both groups sought integration into Indonesian society, their approaches varied significantly. PIN prioritized legal assimilation without imposing cultural uniformity, whereas GIKI-IEV emphasized social work and education as avenues for both integration and cultural adaptation. Despite facing numerous internal and external challenges, the assimilation process accelerated after 1959, coinciding with the dissolution of both organizations. Their contrasting perspectives on national culture and integration fostered internal divisions and influenced the broader contours of Indo-European assimilation in Indonesia.